2008
DOI: 10.1007/s12026-008-8060-y
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity in the pathogenesis of polytropic retrovirus infection in the central nervous system

Abstract: Neuroinflammation, including astrogliosis, microgliosis, and the production of proinflammatory cytokines and chemokines is a common response in the central nervous system (CNS) to virus infection, including retrovirus infection. However, the contribution of this innate immune response in disease pathogenesis remains unresolved. Analysis of the neuroinflammatory response to polytropic retrovirus infection in the mouse has provided insight into the potential contribution of the innate immune response to retrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In Figure 2 it was demonstrated that BMM migration occurs readily toward neuroinflammatory sites. In murine HIVE, the association between such cell migration and neuroinflammation involves activation of astrocytes and microglia and consequent pro-inflammatory CNS responses (3136). In order to determine whether BMM carrying ART can migrate into HIVE affected brain regions we determined NP levels in brain 3 days following intravenous injection of rDHPE-IDV-NP-BMM.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2 it was demonstrated that BMM migration occurs readily toward neuroinflammatory sites. In murine HIVE, the association between such cell migration and neuroinflammation involves activation of astrocytes and microglia and consequent pro-inflammatory CNS responses (3136). In order to determine whether BMM carrying ART can migrate into HIVE affected brain regions we determined NP levels in brain 3 days following intravenous injection of rDHPE-IDV-NP-BMM.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, mechanisms that favour non‐cytolytic viral clearance may preserve postmitotic neurones that could not be replenished or neuronal connections that could not be re‐established may promote latent viral infection. On the other, there is a danger that an associated pro‐inflammatory response would have undesirable consequences of neuroinflammation that has been seen for other viruses (Peterson and Du, ), even for those that are not obviously encephalitogenic (Jurgens et al ., ). As the human brain has a particularly lengthy period of postnatal development (Johnson, ), any sort of neuroinflammatory damage to neonatal brain regions could affect cognitive and psychological functions later in life (Cohly and Panja, ; Hagberg and Mallard, ).…”
Section: Controversy 2: Chikv Infection Of Cns Cell Typesmentioning
confidence: 99%
“…Studies with mouse model of polytropic retrovirus infection, neurovirulent determinants of the polytropic envelope protein and TLR7 KO mice suggest that retroviral pathogenesis in the brain is multifaceted and that cytokine and chemokine production may be only one mechanism involved. TLR7 is a contributing factor to retrovirus-induced neuroinflammation, but other factors can compensate for the lack of TLR7 in inducing both neuroinflammation and neurologic disease [70,71].…”
Section: Retrovirus Infectionmentioning
confidence: 99%